Cost-effectiveness of additional serplulimab to chemotherapy in metastatic squamous non-small cell lung cancer patients - Zheng, Hanrui; Zeng, Ya; Wen, Feng; Hu, Ming (Frontiers in Immunology, 2024)
Objective To estimate the cost-effectiveness of adding serplulimab to chemotherapy for metastatic squamous non-small cell lung cancer (NSCLC) patients in a first-line setting from a Chinese perspective. Methods A three-health state partitioned survival model was constructed to simulate disease development. The clinical data used in the model were derived from the ASTRUM-004 clinical trial. Only direct medical costs were included, and the utilities were derived from published literature. The quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratio (ICER) were employed to evaluate health outcomes. Additionally, a sensitivity analysis was performed to verify the robustness of the results. Results Compared with chemotherapy alone, the addition of serplulimab resulted in an increase of 0.63 QALYs with an incremental cost of $5,372.73, leading to an ICER of $8,528.14 per QALY. This ICER was significantly lower than 3 times China’s per capita GDP. The one-way sensitivity analysis suggested that the utility of PFS was the most sensitive factor on ICERs, followed by the price of serplulimab. Conclusion The combination of serplulimab and chemotherapy has been shown to be a cost-effective initial treatment option for patients with metastatic squamous NSCLC with the commonly accepted willingness-to-pay threshold of 3 times the GDP per capita per QALY in China.